Research Progress on the Mechanism of Itaconate Regulating Macrophage Immunometabolism - Shi, Jia; Cai, Cheng (Frontiers in Immunology, 2022)
The field of immunology is undergoing rapid and dramatic changes. Immunometabolism, a change in metabolic pathways within immune cells, is a key determinant in the activation of immune cells, and intermediates of immunometabolic processes can influence inflammatory gene expression and play a role in inflammation. One of the most representative metabolites is itaconic acid (ITA), which is produced in the tricarboxylic acid cycle (TCA cycle) and plays an important role in macrophage function by regulating macrophage activity through various pathways. In this paper, we review the mechanisms of the metabolite ITA and its derivatives in the regulation of macrophage immune metabolism, intending to gain further insight into the role and mechanisms of this metabolite in macrophages and provide new ideas for the mechanisms and treatment of clinical diseases.